Probing-Prompting Learning Strategy to Increase Biology Learning Activities Student of Class XI IPA 3 at SMAN 5 Kendari - Ahmad, Alfasri (Universitas Sembilanbelas November Kolaka, 2023)
Learning activities are one of the factors that can improve student learning outcomes.However, some students have low learning activity. The aim of the research is toincrease the biology learning activities of class XI IPA3 students at SMA Negeri 5Kendari. This research was carried out in the second semester of the 2013–2014academic year. This type of research is classroom action research (PTK) with threelearning cycles. Each cycle goes through four stages, namely: (1) planning; (2)implementation of actions; (3) observation and evaluation; and (4) reflection. The datasource for this research is students who were measured using learning outcomes testsfor cycles I, II, and III. The data obtained was analyzed using descriptive analysis. Thebiology learning activities of Class 97% Based on the research results, it was concludedthat the probing-prompting learning technique could increase the biology learningactivities of class XI IPA3 students at SMA Negeri 5 Kendari.Keywords: Probing-Prompting Technique , Learning Activities